De pandillas juveniles a bandas criminales: reflexiones sobre su rol en el barrio Mánchester del municipio de Bello (2016)
The municipality of Bello today is an important to investigate the effectiveness of the actors and dynamics of the processes of violence territory which has been immersed since the 80's of the twentieth century. This is the period of inquiry in this academic exercise, which is to be noted that the phenomenon of groups of youth gangs through intimidation and fear has become a recurring problem that afflicts frequently population civil, recipient of indiscriminate violence by these armed organizations. A qualitative methodology of documentary, which in turn is accompanied by observation in situ-in the field-, where illegal armed groups and other parties are involved in the complexity of negotiations and conflicts of local organized crime. Reflections on urban armed conflict and violence by criminal gangs, classified as emerging bands through the lens of national researchers will be raised, and eventually revise critically some official positions on the problems detected in the Manchester neighborhood.